Opini Publik Mahasiswa FISIP UPN Veteran Jakarta terhadap Kampanye Desak Anies Menjelang Pemilu Tahun 2024 - Syahdina Diva Azahwa; Jose Benrivo Sipayung; Huwayda Rahmania; Muhammad Ridhwan Rabbani Firdaus; Gabriella Dofani Natalia Siregar; Restu Rahmawati (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
This study aims to analyze the views of FISIP UPN “Veteran” Jakarta students regarding the “Desak Anies” campaign and its influence on public attitudes and opinions in the context of the 2024 presidential election. The campaign specifically targets young voters through an issue-based dialog approach. The research used mixed methods by combining qualitative and quantitative data obtained from respondents. The survey results showed that 88.5% of students were aware of the campaign, with 83.4% of them supporting the initiative, while 16.6% disagreed. Social media became the main platform for disseminating campaign information, which influenced students' views on the initiative. The campaign was appreciated for being participatory and considered relevant to students' interests and concerns, thus helping to increase their political awareness. This research expands insights into how campaigns targeting young people can influence their political views. Based on the findings, the research recommends that future political campaigns intensify direct engagement with voters through interactive discussion forums. This approach is considered effective in increasing young people's political participation in future elections.